(untitled) (Fiep Bulletin - online, 2012)
Background: The school age coincides with an important phase in human development at some aspects. Many changes occur in the motor activities and eating habits are evident, and in children and adolescents may present a disproportionate increase of body mass and pathological changes in body structure. Objective: To investigate the possible relationship between body alignment and overweight in students of elementary education from a public school. Method: This is a descriptive cross-sectional survey realized with students aged between 11 and 14 years. The sample consisted of 56 male and female students which were evaluated at the school. The overall nutritional status was classified based on the percentile of body mass index (BMI). The postural alignment was evaluated by photogrammetry. The leveling values and alignments were the software analysed using COREL DRAW x 5. The cutoff point considered for flattening corporal was of 3 (three degrees) in relation to 90 of plotting axes y and x, as a measure of abscissas tolerance functional or physiological unevenness. In the analysis of relationship among the variables used the linear Pearson correlation test. Results : There were deviations in girdle waist in 17.9% of students and in the pelvic waist at 14.3%. Overweight was observed in 3.6% of the students. There were no significant statistical correlations among alignment of girdle or pelvic waist and body mass index, gender or age. Conclusion: In the group of children studied there was not relation between postural alignment and overweight.